2019
DOI: 10.1021/acsomega.9b01972
|View full text |Cite
|
Sign up to set email alerts
|

Coordination-Directed Assembly of Luminescent Semiconducting Oligomers and Weak Interaction-Induced Morphology Transformation

Abstract: Luminescent semiconducting oligomers (LSOs) have been one of the most popular molecular materials that can be applied in various fields because of their distinctive optical properties. The study of molecular packing and morphological change of oligomers is essential for the rational design of materials and regulation functions. Herein, we report two novel LSOs (OFBB and OFBT) with a slight difference in chemical structures but show a distinct difference in self-assembly behaviors in the coordination-driven pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…1e) showed fuzzy lattice stripes, which correspond with those previously reported for MOFs. 21,36 Aer pyrolysis, the morphology of the sample remains mostly unchanged, with slight aggregation (Fig. 1b), and the TEM image showed better light transmission (Fig.…”
Section: Characterizationmentioning
confidence: 99%
“…1e) showed fuzzy lattice stripes, which correspond with those previously reported for MOFs. 21,36 Aer pyrolysis, the morphology of the sample remains mostly unchanged, with slight aggregation (Fig. 1b), and the TEM image showed better light transmission (Fig.…”
Section: Characterizationmentioning
confidence: 99%
“…The Fourier transform infrared (FTIR) spectra was introduced to investigate the coordination mode of the carboxyl group in the assembly process. [46,47] The FTIR spectra of the four MOFs showed the v as and v sym peaks of carboxyl group located at around 1585 cm −1 and 1403 cm −1 with △v = 182 cm −1 (Figure 2b), which strongly indicated that the TCPP ligand mainly adopted bridging bidentate coordination mode with the Ce-O clusters in all four MOFs. [48,49] Simultaneously, for the Ce-TCPP, there was a sharp peak located at 1383 cm −1 standing for the v sym of the NO 2 , which indicated that the NO 3 − also participated in the coordination process to balance the charge and fulfill the unsaturated coordination sites of the Ce-O clusters.…”
Section: Assembly and Characterizationsmentioning
confidence: 99%
“…Facile and sensitive analysis methods for in situ and real-time sensing are urgently needed. Fluorescence-based analysis emerged as a promising method to improve safety sensing [ 3 , 4 , 5 , 6 ]. Quantum dots, organic fluorescence dyes, and metallic nanoclusters are classical fluorescent materials; however, these materials inevitably showed weakness such as toxicity, poor selectivity and stability, and high costs [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%